Effect of respiratory virus infections including rhinovirus on clinical status in cystic fibrosis. Issue 2 (August 1995) - Smyth, A R; Smyth, R L; Tong, C Y; Hart, C A; Heaf, D P
Abstract : One hundred and eight patients with cystic fibrosis were investigated over one year to determine whether an association existed between rhinovirus or other respiratory virus infection and clinical status. Forced expiratory volume in one second (FEV1), forced vital capacity (FVC), Shwachman score, Chrispin-Norman chest radiograph score, and percentage weight for height were recorded at the beginning and end of the study; days of intravenous antibiotics were noted. Nasopharyngeal aspirates were taken for viral studies during respiratory exacerbations. Serum was collected at enrollment and 2-6 weeks after each respiratory exacerbation. One hundred and fifty seven exacerbations occurred in 76 patients. Respiratory virus infection was detected in 44 exacerbations and rhinovirus was present in 16% (25/157) of exacerbations. Patients with one or more respiratory virus infections were compared with those who had none. When all respiratory virus infections were considered, patients had a significantly greater deterioration in Shwachman score and received significantly more days of intravenous antibiotics. When rhinovirus was considered separately, patients received significantly more days of intravenous antibiotics, but showed no deterioration in clinical status. However, patients infected with another respiratory virus had a significant decline in FEV1, with trends towards significance for decline in FVC and Shwachman score.